Hijab and Niqab: A Cross-Religious COVID-19 Safety Measure in Madina Zongo - Khamis, Kauthar (Entangled Religions, 2021)
Amidst the COVID-19 pandemic, the use of hijab and niqab (face veil), typically associated with Islamic fundamentalism and banned in some parts of Europe and Africa, have gained currency in multi-religious communities such as Madina Zongo (strangers’ quarters in Hausa) in Accra, Ghana. For some Muslim women in Madina, hijab and niqab appeared to be a perfect replacement for the face mask even without an official statement from medical authorities or state officials on its protective capacity. Wearing these veils allowed them to simultaneously follow their religious tradition and attempt to protect themselves from the disease. Interestingly, some Christian women in the community have also been donning these Muslim veils. Employing Laura Fair’s (2013) proposition that veiling contains a wide range of possible material uses, in this article, I show why and how hijab and niqab are adapted to suit COVID-19 safety measures and appropriated as a face mask by some women in Madina. The chapter also discusses the implications of these innovations in the religiously pluralistic setting of Madina Zongo.